Waiting for Godot : character studies - Lawley, Paul (Bloomsbury character studies., 2013)
This book provides an introductory study of Beckett'smost famous play, dealing not just with the four maincharacters but with the pairings that they form, andthe implications of these pairings for the very idea ofcharacter in the play. After locating Godot within thecontext of Beckett's work, Lawley discusses some ofthe play's puzzles and difficulties-including theabsent ""fifth character"", Godot himself